Severe polyposis in Apc1322T mice is associated with submaximal Wnt signalling and increased expression of the stem cell marker Lgr5. Issue 12 (6th October 2010) - Lewis, Annabelle; Segditsas, Stefania; Deheragoda, Maesha; Pollard, Patrick; Jeffery, Rosemary; Nye, Emma; Lockstone, Helen; Davis, Hayley; Clark, Susan; Stamp, Gordon; Poulsom, Richard; Wright, Nicholas; et al.
Abstract : Background and aims: Adenomatous polyposis coli ( APC ) is a tumour suppressor gene mutated in the germline of patients with familial adenomatous polyposis (FAP) and somatically in most colorectal cancers. APC mutations impair β-catenin degradation, resulting in increased Wnt signalling. The most frequent APC mutation is a codon 1309 truncation that is associated with severe FAP. A previous study compared two mouse models of intestinal tumorigenesis, Apc R850X (Min) and Apc 1322T (1322T), the latter a model of human codon 1309 changes. 1322T mice had more severe polyposis but, surprisingly, these tumours had lower levels of nuclear β-catenin than Min tumours. The consequences of these different β-catenin levels were investigated. Methods: Enterocytes were isolated from 1322T and Min tumours by microdissection and gene expression profiling was performed. Differentially expressed Wnt targets and other stem cell markers were validated using quantitative PCR, in situ hybridisation and immunohistochemistry. Results: As expected, lower nuclear β-catenin levels in 1322T lesions were associated with generally lower levels of Wnt target expression. However, expression of the Wnt target and stem cell marker Lgr5 was significantly higher in 1322T tumours than in Min tumours. Other stem cell markers (Musashi1, Bmi1 and the Wnt target Cd44) were also at higher levels in 1322T tumours. In addition, expression of the Bmp antagonist Gremlin1 was higher in 1322T tumours, together with lower Bmp2 and Bmp4 expression. Conclusions: The severe phenotype caused by truncation of Apc at codon 1322 is associated with an increased number of stem cells. Thus, a submaximal level of Wnt signalling favours the stem cell phenotype and this may promote tumorigenesis. A level of Wnt signalling exists that is too high for optimal tumour growth.